The effectiveness of group problem-solving therapy on women's sexual function and satisfaction after mastectomy surgery - Mahshid Bokaie; Ommolbanin Firouzabadi; Azadeh Joulaee (BMC, 2022)
Abstract Background Breast cancer is the second cause of death and the most common cancer in women worldwide, threatening different aspects of individual and mental health, quality of life, sexual function, and sexual satisfaction. This study aimed to determine the effectiveness of group counseling based on a problem-solving solution on women's sexual function and satisfaction after mastectomy surgery. Methods The present research was an open pilot study, with a pretest, a post-test, and a follow-up period. Of women referred to the Tehran Breast Cancer Institute, 32 were selected using convenience sampling. The group received eight 90-min sessions of problem-solving solution counseling. This approach is based on cognitive-behavioral therapy and can improve an individual's ability to cope with stressful life experiences. The data collection tool was FSFI and sexual satisfaction questionnaires, which were filled before the intervention (baseline), immediately after the intervention, and one month later (follow up). Data analysis was performed using SPSS 21 statistical software application at the certainty level of 95% (P < 0.05). Results The mean FSFI score increased from 18.37 ± 8.35 before the intervention to 20.88 ± 7.67 immediately after the intervention and 22.95 ± 5.79 one month later (P < 0.0001). Also, the mean sexual satisfaction score was 65.27 ± 5.98, 68.08 ± 5.61, and 70.46 ± 5.35 before the intervention, immediately after the intervention, and one month later, respectively (P < 0.05). The results also showed that although the two components of sexual function and satisfaction were statistically significant after sexual counseling, this improvement was not clinically progressive. The mean sexual function and satisfaction score was still low after sexual counseling. Conclusions It was observed that sexual function and satisfaction were improving among the patients after the intervention. Thus, sexual health counseling sessions are recommended for breast cancer patients.